Evaluation of online system acceptance through airlines websites in Malaysia - Dominic, P.D.D. (Institute of Electrical and Electronics Engineers Inc., 2014)
The use of websites and online system is increasing rapidly around the globe. The companies are concerned to provide their customers valuable services and assure to make all informations available on their websites. This paper aims to measure the customer acceptance of online system for the airline websites. As companies are investing high to switch from physical delivery channels to self-service online channels, customer acceptance with online web channel is a major area for research. The proposed research framework added new variable to the technology acceptance model (TAM) to measure the website acceptance. A questionnaire was distributed among the consumers who use the airline websites to book online ticket. The results supported all the hypothesis and gives significant results for measuring customer acceptance of airlines website. Â© 2014 IEEE.